KIPRAH SUPENI PUDJOBUNTORO DALAM BIDANG POLITIK TAHUN 1945-1963 SEBAGAI NARASI PEREMPUAN DALAM PEMBELAJARAN SEJARAH - Bella, Ananda Putri Salsa; Subekti, Arif (Jurnal Pendidikan Sejarah Indonesia, 2023)
Abstract: The involvement and role of women in various fields of life, especially in the political field during the Soekarno Order era, is still less displayed in history. Even though many female figures have made great contributions to Indonesian politics, one of them is Supeni Pudjobuntoro, an ambassador traveling around Indonesia. This article aims to present the female figure as part of agency in historiography. This study describes the history of women through Supeni in the field of politics after independence, precisely in 1945-1963 using historical research methods with five stages, namely topic selection, heuristics in the form of source collection, verification or criticism of sources, interpretation to determine the credibility of historical sources based on facts, and historiography or writing historical facts chronologically. The results of this study show that Supeni had a large share in politics in Indonesia, especially in the era of the Indonesian National Revolution and the leadership of President Soekarno. Supeni was active in organizing the first General Election in 1955 representing the PNI, carried out his foreign policy duties well by lobbying the countries concerned, and contributed to the liberation of West Irian.Abstrak: Keterlibatan dan peran perempuan di berbagai bidang kehidupan terutama di bidang politik pada masa Orde Soekarno masih kurang ditampilkan dalam sejarah. Padahal banyak tokoh perempuan yang memiliki kontribusi besar bagi politik Indonesia, salah satunya adalah Supeni Pudjobuntoro seorang duta besar keliling Indonesia. Artikel ini bertujuan untuk menghadirkan sosok perempuan sebagai bagian dari agensi dalam historiografi. Penelitian ini memaparkan sejarah perempuan melalui Supeni dalam bidang politik masa setelah kemerdekaan tepatnya pada tahun 1945-1963 dengan menggunakan metode penelitian historis dengan lima tahapan yaitu pemilihan topik, heuristik berupa pengumpulan sumber, verifikasi atau kritik sumber, interpretasi untuk mengetahui kredibilitas sumber sejarah berdasarkan fakta-fakta, dan historiografi atau penulisan fakta sejarah secara kronologis. Hasil penelitian ini menunjukkan bahwa Supeni memiliki andil yang besar dalam politik di Indonesia terutama di era Revolusi Nasional Indonesia dan kepemimpinan Presiden Soekarno. Supeni turut aktif dalam penyelenggaraan Pemilihan Umum pertama tahun 1955 mewakili PNI, menjalankan tugas politik luar negeri dengan baik dengan melobi negara-negara yang bersangkutan, dan andil dalam pembebasan Irian Barat.